Does cadre turnover help or hinder China's green rise? Evidence from Shanxi province - Sarah Eaton; Genia Kostka (Frankfurt School of Finance & Management, 2012)
China's national leaders see restructuring and diversification away from resourcebased, energy intensive industries as central goals in the coming years. This paper argues that the high turnover of leading cadres at the local level may hinder state-led greening growth initiatives. Frequent cadre turnover is intended to keep local Party secretaries and mayors on the move in order to curb localism and promote compliance with central directives. Yet, with average term lengths of between three and four years, local leaders' short time horizons can have the perverse effect of discouraging them from taking on comprehensive restructuring, a costly, complex and lengthy process. On the basis of extensive fieldwork in Shanxi province during 2010 and 2011, the paper highlights the salience of frequent leadership turnover for China's green growth ambitions.
Keywords: D78; D73; O18; R58; Q48; Q58; 330; Local state; China; policy implementation; governance; cadre rotation